ANALISIS PRESTASI BELAJAR SISWA PELAJARAN EKONOMI, STATUS SOSIAL EKONOMI ORANG TUA DAN BIMBINGAN BELAJAR (STUDI PADA SMA NEGERI 10 KOTA TANGERANG) - Saepuloh, Dadang (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2019)
This study aims to determine the effect of parental socioeconomic status and tutoring on students' learning achievement of economic subjects in class XI of the social studies program at SMA 10 Tangerang. The sample in this study were 54 students in SMA 10 Tangerang. This research is ex-post facto research. The variables of this study are economic learning achievement, socioeconomic status, and tutoring. Data collection techniques use questionnaires and documentation. The analytical method used is multiple regression analysis. From the results of the study, the following conclusions are obtained: (1) socioeconomic status does not affect the learning achievement of Economics subjects which is indicated by a sig value of 0.184 more than 0.1. (2) learning guidance has an effect on economic learning achievement which is indicated by a sig value of 0.030 smaller than 0.1. (3) socioeconomic status and tutoring have a positive effect on economic learning achievement which is indicated by a sig value of 0.046 smaller than 0.1. R2 value of 0.113 means that 11.3% of the learning achievement of Economics subjects is explained by socioeconomic status and tutoring. While 88.7% is explained by other factors not examined in this study.